(untitled) (Bangladesh Journal of Plant Taxonomy, 2025)
The new species Lycium mellitum J. Z. Dong (Solanaceae) is established and illustrated from Qinghai province of China. It has a close association with L. ruthenicum and L. ostrum J.Z. Dong, but is distinguished by several morphological characters: stems much branched, thorns at nodes or not, usually clustered with leaves and flowers; leaves narrowly linear, fleshy, gray, usually apically light yellow; pedicel 10-20 mm long; berries orange-yellow, nearly transparent, inside placenta faintly visible; seeds 1-5, rarely more, light brown. Bangladesh J. Plant Taxon. 32(1): 123-127, 2025 (June)